PEER GROUP SUPPORT DALAM MENINGKATKAN PERILAKU PENCEGAHAN ANEMIA IBU HAMIL - Ria Ines N; Kusnanto Kusnanto; Ni Ketut Alit (Universitas Airlangga, 2014)
Pregnancy is a new period of life, where the baby growth before they were ready to born. Pregnancy closely associated with anemia, which Hb amount of mother under 11gr% on first and third trimester, and under 10.5gr% on second trimester. Lack of knowledge can lead to inappropriate attitudes and actions in reduce the incidence of anemia. Peer group support which is discuss about the same health problem was untried before. The purpose of this study was to analyze the influence of peer group support to knowledge, attitudes, and actions of pregnant women on anemia prevention during pregnancy. This is a pre-experiments study with one group pretest-posttest design. Population of this study consist of 156 pregnant women. This research using purposive sampling method. The number of samples is 16 respondents. Independent variable of this study is peer group support, while the dependent variables are knowledge, attitudes and actions. Data collected by observation and questionnaires. The data analyzed with Wilcoxon Signed Rank Test with significance level p < 0.05. Peer group support has a significant influences in increasing knowledge level, attitudes and actions of pregnant woman. Knowledge analysis test results: 0.001, attitudes: 0.001 and actions: 0.001. It shows there are significant differences of knowledge, attitudes and actions between before and after peer group support. Peer group support can improve knowledge, attitudes and actions of pregnant woman on anemia prevention. Peer group support helps pregnant woman to get many informations from the other members and also help them to find a way out of her problems about anemia prevention. This may be a suggestion for the health provider to organize peer group support regularly to increase the knowledge, attitudes and actions of pregnant woman in effort to decrease the incidence of anemia in pregnant woman.